Ang Panulaan ni Maria Lorena Barros [The Poetry of Maria Lorena Barros] - Hernando, Pauline Mari F. (Philippine Humanities Review; Vol 15 No 2 (2013), 2015)
Maria Lorena Barros is one of the founders and leaders of the first allwomen revolutionary movement in the country, the MAKIBAKA or Makabayang Kilusan ng Bagong Kababaihan. Her poetry, which summarizes the involvement of women in the revolutionary movement in the country, represents the progressive.revolutionary text. Such text clarifies the role and relevance of the armed struggle in achieving national sovereignty and democracy. In this paper, Barros’s poems are divided according to the development of her social consciousness, including her participation in progressive organizations and activities. These poems are considered revolutionary in the sense that, they speak of the real principle and ideology of revolutionary struggle; they provide critique on the root causes of the stuggle by the Filipino masses; they testify to the relevance of armed struggle against all forms of oppression by the reactionary government; and, they provide alternative means in encouraging people to fight against imperialism, feudalism, and bureaucrat capitalism. Barros’s masterpieces serve as a worthy challenge to the existing elitists’ theories that serve only the fascists and the ruling classes. The revolutionary text exists to expose the genuine and fundamental source of national crises and encourages collective movement in achieving authentic freedom from a semi-colonial and semi-feudal society. Keywords: Revolutionary Text, Women, Language, Struggle, Poetry